Analysis Return on Assets in Transportation and Logistics Sector Companies on the Indonesia Stock Exchange - Anisa Rahmawati; Bayun Matsaany; Khairul Alim (Pusat Riset dan Inovasi Nasional, 2025)
Return on assets is a financial ratio used to measure a company's ability to generate overall profits. This research aims to see and analyze the effect of the current ratio, debt-to-asset ratio, and total assets turnover on return on assets in the transportation and logistics companies listed on the Indonesia Stock Exchange in 2017-2022. The research method used in this research is quantitative. Data were analyzed using multiple linear regression analysis with the help of SPSS 25 and hypothesis testing using simultaneous tests (F test) and partial tests (t-test). The data used is secondary data obtained from the company's published financial reports. The sampling technique in this research was a purposive sampling method based on certain criteria. The results show that simultaneously the current ratio, debt-to-asset ratio, and total assets turnover influence the return on assets of 94.5%. Meanwhile, partially, the debt-to-asset ratio affects the return on assets while the current ratio and total assets turnover do not affect the return on assets.